STUDI PENURUNAN KROMIUM DAN NIKEL DALAM PENGOLAHAN LIMBAH CAIR ELEKTROPLATING DENGAN METODE ELEKTROKOAGULASI - Wenny Dwi Retna Prihartanti; Ganjar Samudro; Junaidi Junaidi (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTEnvironmental pollution that caused by electroplating waste disposal into the environment can cause harmful effects for human life. Before it is discharged into the environment need the method to treatment this waste. Electro coagulation is one of the wastewater treatment methods which are interchangeable to treat the electroplating industrial waste. This electroplating waste contain heavy metals such as chromium (Cr), Nickel (Ni) and Copper (Cu). Electro coagulation experiments have been conducted with the independent variable which are the type of plate alumunium (Al) and Iron (Fe), and also Current density 40 mA/cm2, 50 mA/cm2, 60 mA/cm2 and 70 mA/cm2. This study uses a powerful current 5 Amperes, time operation 120 minutes, with the sampling time every 15 minutes, number of plate 4 pieces, 2 cm distance between electrodes. Based on experiments have been conducted that obtained best results at the highest current density removal efficiency of chromium allowance 99,60 % for using iron electrodes. Whereas for nickel removal, the best results at the highest current density removal efficiency of nickel allowance 96,20 % for using alumunium electrodes. Other measurements in this study that may affect the process of electro coagulation include pH, temperature, TSS, TDS and turbidity.